Tranformasi Penetapan Ibu Kota Negara Dalam Pelayanan Publik Terkait Infrastruktur di Kabupaten Penajam Paser Utara - Andri, Yayan; Sofyan, Mety Mediyastuti; Yusuf, Riki Maulana; Rahardian, Ramaditya (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2025)
This study describes the Impact of the Determination of the National Capital City on the Quality of Infrastructure Services of the National Capital City in Penajam Paser Utara Regency (Roads, Land Acquisition, Dams, Toll Roads) where Infrastructure plays a role in various sectors of life, especially for the local community of Penajam Paser Utara Regency who are directly affected by the development of the New Capital City infrastructure. Infrastructure development is one of the important role holders in life, especially road infrastructure, apart from being a means and infrastructure for transportation, it is also a supporting aspect in the distribution of goods and other supporting facilities. The research method used in this study is descriptive analysis with the type of research being qualitative. The results of the study, the success or failure of the development of the New Capital City, is very much determined by how the leadership relay will go forward which will have a direct impact on the quality of public services provided to the residents of Penajam Paser Utara which is currently underway. such as road infrastructure and furthermore will have an impact on the quality of basic services such as education, health and infrastructure.